Standardization of skin cleansing in vivo: part I. Development of an Automated Cleansing Device (ACiD). Issue 2 (19th October 2013) - Sonsmann, F. K.; Strunk, M.; Gediga, K.; John, C.; Schliemann, S.; Seyfarth, F.; Elsner, P.; Diepgen, T. L.; Kutz, G.; John, S. M.
<x xml:space="preserve">Abstract</x> Background To date, there are no legally binding requirements concerning product testing in cosmetics. This leads to various manufacturer‐specific test methods and absent transparent information on skin cleansing products. A standardized in vivo test procedure for assessment of cleansing efficacy and corresponding barrier impairment by the cleaning process is needed, especially in the occupational context where repeated hand washing procedures may be performed at short intervals. Methods For the standardization of the cleansing procedure, an Automated Cleansing Device (ACiD) was designed and evaluated. Different smooth washing surfaces of the equipment for ACiD (incl. goat hair, felt, felt covered with nitrile caps) were evaluated regarding their skin compatibility. Results ACiD allows an automated, fully standardized skin washing procedure. Felt covered with nitrile as washing surface of the rotating washing units leads to a homogenous cleansing result and does not cause detectable skin irritation, neither clinically nor as assessed by skin bioengineering methods (transepidermal water loss, chromametry). Conclusions Automated Cleansing Device may be useful for standardized evaluation of the cleansing effectiveness and parallel assessment of the corresponding irritancy potential of industrial skin cleansers. This will allow objectifying efficacy and safety of industrial skin cleansers, thus enabling market transparency and facilitating rational choice of products.